PEMBELIAN KONSUMEN MENGGUNAKAN ALAT-ALAT UKUR, TAKAR, TIMBANG DAN PERLENGKAPANNYA (UTTP) YANG BERTANDA TERA SAH DI KABUPATEN BOALEMO - Nurhayati Umar Djafar; Moh. Afan Suyanto; Deby R. Karundeng (Bisnis-Net, 2023)
The purpose of this study was to analyze consumer behavior towards consumer purchasing decisions using measuring instruments, measures, weights and equipment (UTTP) which are marked as valid in Boalemo Regency. The data used in this study is primary data sourced from filling out questionnaires. The research population is 75 respondents using the incidental method. The analysis technique used to answer research problems and test hypotheses is multiple regression analysis with the help of Statistical Product Service Solution (SPSS) software. The findings of this study are (1) cultural factors have a positive and significant effect on purchasing decisions, (2) social factors have a positive and significant effect on purchasing decisions, (3) personal factors have a positive and significant effect on purchasing decisions, (4) psychological factors have a positive effect and significant to the purchase decision.